A fast acoustic emission beamforming localization method based on Hilbert curve. (1st November 2019) - He, Tian; Tai, Junfei; Shan, Yingchun; Wang, Xiaoran; Liu, Xiandong
Highlights: The Hilbert curve is introduced to improve the efficiency of AE beamforming. The 'Nine-Four bisection' method is proposed to overcome the boundary problem. The HCBF maintains the original localization accuracy and reliability. The more grids, the higher the HCBF efficiency. Abstract: The low efficiency of the acoustic emission (AE) beamforming localization method in large-scale structural monitoring seriously restricts its application in practice. The Hilbert curve is introduced to improve the computational efficiency of AE beamforming method in this paper. Firstly, the Hilbert curve is introduced to traverse the monitored area, and quickly capture the approximate position of the AE source based on Beamforming. Then, the 'Nine-Four bisection' method is proposed to overcome the boundary problem in region division. Finally, the Hilbert curve-beamforming method (HCBF) is verified by simulation and experiment data. The results show that, the presented method not only greatly improves the computational efficiency, but also maintains the original localization accuracy and reliability. It creates a prerequisite for the further promotion and development of the beamforming method in the field of AE source localization in large-scale structural health monitoring.